posted by cathy .
I need to find the derivative and can't do them when they are raised to powers? Thank You.
m(x)x^5 - 5x^3+7x -4)^10 (4x^9 +19)^23 this on is tuff!
Your brackets don't match , also there is no equal sign
is it ...
m(x) = (x^5 - 5x^3 + 7x - 4)^10 * (4x^9 + 19)^23 ??
(the * means multiplication)
the key, however, is the chain rule. If
f = u^n, then
df/dx = nu^n-1 * du/dx
It's just the familiar power rule, but you have to multiply by the derivative of what's raised to the power.
For example, if you have
f(x) = (3x^2-4x+5)^5, then
let u = 3x^2 - 4x + 5.
Then all you have is
f(x) = u^5
df/dx = 5u^4 du/dx
But that's easy, because du/dx = 6x-4, so the final answer is
df/dx = 5(3x^2-4x+5)^4 (6x-4)